25-Hydroxycholesterol and inflammation in Lovastatin-deregulated mevalonate pathway. (November 2017) - Tricarico, Paola Maura; Gratton, Rossella; Braga, Luca; Celsi, Fulvio; Crovella, Sergio
Graphical abstract: Abstract: Mevalonate pathway deregulation has been observed in several diseases, including Mevalonate kinase deficiency (MKD). MKD is a hereditary auto-inflammatory disorder, due to mutations at mevalonate kinase gene ( MVK), encoding mevalonate kinase (MK) enzyme. MVK mutations have been reported as associated with impairment of mevalonate pathway with consequent decrease of protein prenylation levels, defective autophagy and increase of IL-1β secretion, followed by cell death. Since 25-hydroxycholesterol (25-HC), a metabolite of cholesterol, can suppress IL-1β production, thus reducing inflammation, we evaluated the effect of 25-HC in an in vitro model of mevalonate pathway alteration, obtained using Lovastatin. Human glioblastoma cell line (U87-MG) was chosen to mimic, at least in part, the central nervous system impairment observed in MKD; 25-HC effects were evaluated aimed at disclosing if this compound could be considered as novel potential drug for MKD. Our results showed that 25-HC is able to reduce inflammation but it is ineffective to restore autophagy flux and to decrease apoptosis levels, both caused by lower protein prenylation; so, in spite of its anti-inflammatory action it is not useful to rescue defective prenylation/autophagy impairment-driven apoptosis in Lovastatin impaired mevalonate pathway. We hypothesize the presence in the mevalonate pathway of alternative mechanisms acting between inflammation and apoptotic autophagy impairment.